Refining composition skills : academic writing and grammar - Smalley, Regina L., ....-; Ruetten, Mary K., ....-; Kozyrev, Joann Rishel, ....- (Boston : Heinle ELT, 2011)
The new edition of this best-selling series combines comprehensive development and practice in the rhetorical modes while integrating instruction in reading, grammar, critical thinking, and vocabulary development. -Developing Composition Skills focuses students on narrating, describing, analyzing, comparing and contrasting, classifying, and evaluating at the paragraph level and offers a complete introduction that bridges the gap between the paragraph and the essay level. -Refining Composition Skills develops essay writing skills needed for success at the college level by thoroughly reviewing and presenting the following rhetorical modes: compare and contrast, example, classification, process analysis, cause and effect, and argument.
Keywords: Schrijfvaardigheden Engels